Automatic cruise system for water quality monitoring - Zhu, Chengyun; Liu, Xingqiao; Chen, Hailei; Tian, Xiang (International Journal of Agricultural and Biological Engineering, 2018)
The range of unit fixed-point measurement on water quality monitoring system is limited, and the cost for multipoint measurement is high. In order to solve these problems, the automatic cruise system for water quality monitoring was designed. Sage-Husa adaptive Kalman filtering algorithm was adopted to correct the error in GPS positioning. The boat was equipped with ship control module, water quality parameters acquisition module, power-supply module, GPS module and GPRS-DTU packet data transmission module. An Android application was developed so that individual users can use smartphone to communicate with the boat at all time and places. The results show that the boat can basically cruise in the set route to monitor the water quality. In a 4 m2 aquatic plants areas, the dissolved oxygen monitored in different time were about 10.2%, 8.5% and 8.3%, respectively, higher than other areas, and the pH values were 4.1%, 3.8% and 3.7% higher than those in other waters, which shown that plants photosynthesis released oxygen consumption of carbon dioxide will affect the dissolved oxygen content and pH value. This system can widen the measurement range, and lower the measuring cost that can be widely used in the water quality monitoring in aquaculture and river management.Keywords: water quality monitoring, GPS, automatic cruise, Android mobile clientDOI: 10.25165/j.ijabe.20181104.2658Citation: Zhu C Y, Liu X Q, Chen H L, Tian X. Automatic cruise system for water quality monitoring. Int J Agric & Biol Eng, 2018; 11(4): 244-250.